Little VI línea danza clásica (2019)
The present project of degree deals with how to avoid the injuries and inflammations in the essays of the infantile classic dance by means of the clothes where the creation of the Little Vi brand was developed, where the purpose is to create costumes for children's essays focused on dance classic, in order to meet the needs of the consumer providing safety and ergonomics when performing their physical activity.The design alternative focused on the use of the technology method by means of the microcapsules with natural medicinal creams that will be implemented in the fabrics with which the classical dance rehearsal costumes will be made in order to avoid these types of problems. of the injuries and inflammations that occur frequently in children. The development of the trend was developed through a research on the WGSN platform on the utopian technology trend that is a futuristic and minimalist trend.Taking into account the research of the target market that was done through interviews and surveys, some determinants and requirements were made for the development of design alternatives where a final validation of the design alternative will be carried out to make the proposal.